THE FUNCTIONAL STATUS AND CARDIOHEMODYNAMICS OF THE RIGHT PARTS IN PATIENTS WITH COMPENSATE CHRONIC PULMONARY HEART UNDER LONG-TERM USING OF CANDESARTAN - Середюк, В. Н. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
With the aim to investigate of the influence of long-term (during 6 months) using of Candesartan at the functional status of right heart’ parts and level of secondary pulmonary hypertension, the 55 patients (43 males and 12 females, middle age – 43,7±3,4 years) with chronic obstructive lung diseases, complicated by chronic pulmonary heart (stage of compensation) were observed. All patients were divided into two groups: I (basic) – 29 patients have used candesartan (Candesar, “Ranbaxy”, India-USA-Canada) in dose diapasons 4-32 mg per day and basic therapy of COPD (M-cholinolytics, beta2-agonists, mucolytics, methylxantines); II (control) – 26 patients with basic therapy of COPD only. Established, that using of candesartan with basic therapy of COPD during 6 months improved of functional status of right parts of heart, reversed of right ventricle remodeling, decreased its hypertrophy and dilatation, regressed of pulmonary hypertension.